The Space of Time - Juhani Pallasmaa (Oz, 1998)
We do not live in an objective material world. We live in mental worlds in which the experienced, remembered and dreamed, as well as the present, past and future, constantly fuse into one another. We transform time and space through imagination and dreaming, into the specific human mode of existence—the world of possibilities.